2019
DOI: 10.1039/c8se00552d
|View full text |Cite
|
Sign up to set email alerts
|

3D-porous electrocatalytic foam based on Pt@N-doped graphene for high performance and durable polymer electrolyte membrane fuel cells

Abstract: A new class of sustainable electrocatalysts based on Pt@N-doped graphene foam is developed for the oxygen reduction reaction of PEMFCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…The urea solution was stirred for 5 min, while ammonia was dropped until the pH reached 10. Subsequently, 2 mL of hydrated hydrazine was added as reducing agent, and afterwards the solution was introduced into the autoclave [ 14 ]. In order to prevent the graphene foam from breaking, a special Teflon support was designed for its slow diving and supporting during the hydrothermal process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The urea solution was stirred for 5 min, while ammonia was dropped until the pH reached 10. Subsequently, 2 mL of hydrated hydrazine was added as reducing agent, and afterwards the solution was introduced into the autoclave [ 14 ]. In order to prevent the graphene foam from breaking, a special Teflon support was designed for its slow diving and supporting during the hydrothermal process.…”
Section: Methodsmentioning
confidence: 99%
“…Incorporating nitrogen atoms into the graphene structure is considered a route to creating a valance band and, consequently, to change its electronic structure [ 13 ]. Thus, it is possible to tune the electrochemical properties of nitrogen-doped graphene to synthetize a stable and highly efficient non-metallic catalyst for oxygen reduction (ORR) [ 14 ], hydrogen production (HER) [ 15 , 16 ], and oxygen production (OER) reactions [ 17 ]. Li et al [ 15 ] indicated that the free-standing N-enriched carbon foam@WS 2 nanoflakes prepared by a thermal evaporation process, can be used as the working electrodes for HER in water splitting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there are different opinions about which N types are determinative for ORR activity. It is generally believed that pyridinic N and pyrrolic N are the main factors that improve the ORR electrocatalytic activity, forming a strong interaction with metal nanoparticles, while graphitic N has a positive effect on the improvement of the catalyst conductivity, and quaternary N can promote the adsorption and dissociation of O2 [95,96,99,100]. In contrast, different perspectives are inevitable, Zhao et al [101] and Hattig et al [102] hold the opinion that pyridinic N was the key to enhancing ORR activity.…”
Section: Nitrogen-doping Carbonmentioning
confidence: 99%
“…Well-known methods of synthesis produce three-dimensional graphene materials effectively, but they are too expensive and require specialized equipment. The assembly of graphene flakes 25 , 26 by the hydrothermal method 27 is also popular, although not without disadvantages; self-organization of graphene sheets is the most common problem that researchers want to eliminate 28 . The microwave method 29 , 30 supports the synthesis of graphene, combining many advantages: it is fast, simple, does not require specialized equipment, and the starting material for foam production can be expanded graphite 31 or sucrose 32 .…”
Section: Introductionmentioning
confidence: 99%